Evaluation of the factors determining the profit of lamb fattening - Fenyves, Veronika (Acta Agraria Debreceniensis, 2007)
Lamb fattening in the past 8 years was generally a loss-making business and it was worth selling only in two weight categories – at 24-27 kg and at 27-30 kg –, because in this categories a modest profit could be achieved in most of the years. Selling lambs at 20-24 kg-weight provides a proper income for the sheep farmers only if the milking period is prolonged. If the lambs are weaned at a weight of 16-20 kg, then they are not worth selling them in this weight category. The profit of fattening ram lambs is higher and safer than that of ewe lambs. In Hungary, the profitability of lamb fattening is insecure due to the large variability in purchase prices and the instability of the market. When studying the profitability of the two genders combined, it can be stated that the summer fattening period was the most profitable, while if only the rams are considered then the profitability of the autumn and spring periods was the highest, which is due to Easter and Christmas lambs. Based on our results, we came to the conclusion that ewe lambs and rams should be sold at a lower and higher weight category, respectively.